Counterparty credit risk and credit value adjustment : a continuing challenge for global financial markets - Gregory, Jon, 1971- (Wiley finance series., 2012)
A practical guide to counterparty risk management and credit value adjustment from a leading credit practitioner Since the collapse of Lehman Brothers and the resultant realization of extensive counterparty risk across the global financial markets, the subject of counterparty risk has become an unavoidable issue for every financial institution. This book explains the emergence of counterparty risk and how financial institutions are developing capabilities for valuing it. It also covers portfolio management and hedging of credit value adjustment, debit value adjustment, and wrong-way counterpar.